De stille refolutie - Fred van Lieburg (Religie & Samenleving)
Several studies have been published about ‘silent (r)evolutions’ in different wings of Dutch Reformed Protestantism, such as synodaal-gereformeerden (Reformed Churches in the Netherlands), vrijgemaakt-gereformeerden (Reformed Churches in the Netherlands [Liberated]) and hervormd-gereformeerden (Reformed Bond within the Protestant Church in the Netherlands). They suggest slow shifts within partly ‘pillarized’ church groups from orthodox Calvinist beliefs to modern religious views. The so-called bevindelijk (pietistic) gereformeerden, reformatorischen (‘refo’s’) or Dutch Bible Belt communities seem to be a special case in point. Scattered among the mainstream Protestant Church in the Netherlands and various small and strict Reformed denominations, they are represented by the Staatkundig Gereformeerde Partij. This ‘Political Reformed Party’ was founded by G.H. Kersten in 1918 as mobilization of conservative, pietistic and anti-papist people, rejecting social assurance, vaccination and women suffrage, and developing into a minor pillar or reformatorische zuil in the 1970s. This essay builds upon contemporary observations of the SGP in its starting period and in its recent presentation as well. It argues for a development from a critical or ‘revolutionary’ positioning in the democratic scene during the 1920s to a constructive participation in the political process since the 1990s. However, the ‘silent revolution’ of the staatkundig gereformeerden or the social and cultural emancipation of the bevindelijk gereformeerden is accompanied by signs of ‘anti-government sentiments’ and serious resistances within certain ‘refo’ communities. The artificial word refolutie (refolution) plays on the suggestion of a delayed and specific way of emancipation, integration and ‘depillarization’ of this religious minority. Further research is encouraged in order to understand and explain the complicated and contradictory experience of these compromisers between orthodoxy and modernity.